Molecular Cytogenetic Study of Chronic Lymphocytic Leukemia Patients Diagnosed in Erbil City Using Fluorescence in Situ Hybridization (FISH) Technique (Razi Medical Journal, 2025)
Abnormalities in chromosomes were assessed using cytogenetic and molecular cytogenetic analyses utilizing the FISH technique on blood samples from patients diagnosed with chronic lymphocytic leukemia. The study included the selection of 50 patients (32 males and 18 females) for both the early diagnosis phase (before therapy) and the treatment phase, examining various factors such as sex, age, and occupation. The results revealed that most patients in the over-70 age demographic are male. The majority lacked a familial history of this condition. Patients with chronic lymphocytic leukemia exhibited a higher prevalence of the chromosomal defect deletion (13) (q14) at 43.8%, followed by deletion (11) (q23) at 18.8%. A trisomy 12 alteration was observed at 12.5%, along with a loss on chromosome 17, also present at 12.5%. Tetraploidy occurred seldom (6.2%), notwithstanding the existence of chromosomal defects, specifically deletions (6) at q25-q27. The current study indicates that structural chromosomal modifications were more prevalent than numerical changes regarding chromosomal aberrations, with both types associated with chronic lymphocytic leukemia.
Keywords: Cytogenetic study, FISH Technique, Chronic Lymphocytic Leukemia, Deletion, Trisomy 12